Influence of yttrium doping on microstructural and optical properties of FTO thin films prepared by nebulizer spray technique. (September 2020) - Thomas, R.; Mathavan, T.; Shkir, Mohd.; AlFaify, S.; Kim, Hyun-Seok; Kathalingam, A.
Highlights: Novel rare earth Yttrium doped FTO thin films prepared using Nebulizer spray method is reported. It is the first report on Yttrium doping with FTO in spray method. Reported detailed electrical and optical properties of different doping concentration effect. Obtained high conductivity with high transparency equivalent to commercial FTO, an attractive feature for a TCO material. Abstract: This work demonstrates a novel attempt to enhance the optical properties of fluorine doped tin oxide (FTO) by doping rare earth element yttrium (Y) in different concentrations (0–1.5 wt.%) using nebulizer spray pyrolysis technique at 450 °C. The variation in structural, morphological, optical and electrical properties of the films due to doping are analyzed using X-ray diffraction (XRD), Raman spectroscopy, Atomic force microscope (AFM), Energy dispersive X-ray analysis (EDAX), UV–vis spectroscopy, Photoluminescence and Hall Effect measurements. The prepared films are in polycrystalline nature with tetragonal structure and its crystallite size is reduced with doping. Raman analysis shows peaks at 444 cm −1, 570 cm -1 and 790 cm -1 corresponding to Eg, Eu and B2g vibrational modes for the Y-doped FTO films. AFM measurements displays decrease in surface roughness for the doped films. Optical transmittance spectrum exhibits an increase of transmittance from 60 % to 77 % for the host material to 1.5 wt.% Y doped FTO with increase of band gap from 3.88 eV to 3.96 eV. The different optical constants such as refractive index, extinction coefficient, real and imaginary parts of dielectric constants are also reported. Ultraviolet emission at 370 nm is observed in PL spectra related to near band edge emission. Large carrier concentration 6.02 × 10 19 cm -3 and small resistivity value 1.97 × 10 -3 Ω-cm are observed for 1.5 wt.% Y doped FTO thin film. The obtained figure of merit value 1.9 × 10 -3 Ω -1 is perfectly suitable for optoelectronic applications.